A nationwide population-based surveillance of invasive Haemophilus influenzae diseases in children after the introduction of the Haemophilus influenzae type b vaccine in Japan. Issue 38 (11th September 2018) - Suga, Shigeru; Ishiwada, Naruhiko; Sasaki, Yuko; Akeda, Hideki; Nishi, Junichiro; Okada, Kenji; Fujieda, Mikiya; Oda, Megumi; Asada, Kazutoyo; Nakano, Takashi; Saitoh, Akihiko; Hosoya, Mitsuaki; et al.
Highlights: An active surveillance through a phased introduction of the Hib vaccine in Japan was studied. Hib disease incidence decreased significantly after vaccine introduction. Hif and non-typeable H. influenzae were isolated from a few cases. Serotype replacement was not observed after the introduction of the Hib vaccine. Continuous capsular typing and strain identification surveillance is important. Abstract: Background: Haemophilus influenzae type b (Hib) vaccine was introduced as a voluntary vaccine in December 2008 and was included in the national routine immunization program in April 2013 in Japan. Currently, no nationwide data are available to evaluate the effectiveness of Hib vaccine in Japan. Methods: To evaluate the effectiveness of Hib vaccine in Japan, nationwide active population-based surveillance of culture-proven invasive infections caused by H. influenzae in children was performed in 2008–2017 in 10 prefectures in Japan (covering approximately 23% of the total Japanese population). Clinical data were recorded on a standardized case report form. Capsular type and antimicrobial susceptibility of the H. influenzae isolates were examined. The incidence rate ratio (IRR) and its confidence interval (CI) were calculated to compare data from 5 years before and that from after the introduction of the national routine Hib vaccine immunization program. Results: During the 10-year study period, 566 invasive H. influenzae disease cases including 336 meningitis cases were identified. The average number of invasive H. influenzae disease cases among children <5 years of age during 2013–2017 decreased by 93% (IRR: 0.07, 95%CI 0.05–0.10, p < 0.001) compared with those occurring during 2008–2012. Hib strains have not been isolated from invasive H. influenzae disease cases since 2014; however, non-typeable H. influenzae and H. influenzae type f isolates have been noted as causes of invasive H. influenzae diseases among children <5 years in the post-Hib vaccine era. Conclusions: After the governmental subsidization of the Hib vaccine, invasive Hib disease cases decreased dramatically in the study population, as per our surveillance. Continuous surveillance is necessary to monitor the effectiveness of Hib vaccine and for detecting any emerging invasive capsular types.